(untitled) (Journal of the College of Education for Women, 2024)
Universities play a unique role in providing a type of education that can present business models in a way that may contribute to driving economic growth. Therefore, university education and development are two sides of the same coin, and this coin is the human resources, i.e., without it, there will be no development, especially since there is a relationship of influence and impact between the student’s personality and the university, which results in the student acquiring skills and experiences that will help him/her in the end to carry out his/her role in serving his/her community. Many entrepreneurs among graduates from colleges of education lack the skills of creativity, innovation, and initiative to pave the way in this life, as government institutions are no longer able to provide the jobs required for the queues of graduates searching for job opportunities. This paper aims to know the role of Colleges of Education in achieving university entrepreneurial education, and knowing the obstacles to teaching entrepreneurship at the university. Both researchers followed the Descriptive Analytical Approach in this paper, and among the most important proposals is: providing Academic Courses concerned with developing entrepreneurship skills, entrepreneurial spirit, as well as the culture of freelancing for students.